Blood eosinophil counts in COPD patients compared to controls. Issue 4 (24th October 2019) - Kolsum, Umme; Southworth, Thomas; Jackson, Natalie; Singh, Dave
In patients with COPD, blood eosinophil counts can predict the effects of inhaled corticosteroids (ICS) on exacerbation rates [1–4]. Blood eosinophil counts are now recommended by the Global initiative for the management of Obstructive Lung Disease (GOLD) as a biomarker to help guide ICS use in clinical practice [5]. Blood eosinophil counts are increased in COPD patients compared to healthy controls http://bit.ly/2ML6pzZ